MalFam: a comprehensive study on malware families with state-of-the-art CNN architectures with classifications and XAI - Haque, Abid Hossain; Jahin, Labiba Ifrit; Katib, Sheikh Yasir Hossain; Tuhee, Saiwara Mahmud; Tasnia, Maisoon (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.